2014
DOI: 10.1093/geronb/gbu149
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks and Health Among Older Adults in Lebanon: The Mediating Role of Support and Trust

Abstract: Results document links between the social networks and health of older adults in Lebanon within the context of ongoing demographic transitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 33 publications
1
33
1
Order By: Relevance
“…The reduced impact of this cognitive reserve indicator on cognition in our study was surprising since social activities have a significant influence on the mental and physical health among Lebanese individuals. Given the diverse and changing social structure in Lebanon, and since the older adults in this country are family oriented, investigating social typology and function as cognitive reserve factors may yield better insight to answering our question (Webster et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reduced impact of this cognitive reserve indicator on cognition in our study was surprising since social activities have a significant influence on the mental and physical health among Lebanese individuals. Given the diverse and changing social structure in Lebanon, and since the older adults in this country are family oriented, investigating social typology and function as cognitive reserve factors may yield better insight to answering our question (Webster et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then we used a door-to-door survey to investigate all older adults of each village group, with the following inclusion criteria. (1) Local residents; (2) age ≥ 60 years old, referring to the criteria for defining older adults in Chinese authorities, such as China National Bureau of Statistics [34] and the China National Committee on Aging [35], and previous studies [10,16,20,26]; (3) normal intelligence, no problem with language communication; and (4) willing to participate in the survey. The questionnaire designed specifically for this study primarily includes items related to personal sociodemographic characteristics, social network, social support, depression, and self-rated health.…”
Section: Data Sample and Methodsmentioning
confidence: 99%
“…Other scholars have analyzed the impact of social network types on health via additional pathways, such as mediating effects [10,26]. Webster et al [26] examined the mediating role of social support in the association of social network types with depressive symptoms and health limitations, and found that social support only mediated the link between social network types and health limitations. In addition, the majority of studies analyzed the relationship between social networks and social support as well as the impact of social support on health [4,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limited data available from the Middle East and North Africa region suggest a positive association between lack of community services, poor housing quality, a derelict infrastructure, and the prevalence of chronic illness (Habib et al 2009;Habib et al 2011). Some studies have gaged the accumulated burdens of unemployment and unpaid domestic labor, as well as shrinking social networks, on the health of older persons (Habib et al 2006;Webster et al 2015). Others portrayed the gendered dimensions of poor SRH among older persons in urban and informal neighborhoods (Ahmad et al 2013;Chemaitelly et al 2013).…”
Section: Mechanisms Linking Social Capital and Economic Capital To Hementioning
confidence: 99%